Política educacional na pós-graduação em Educação: uma análise a partir da trajetória coletiva dos pesquisadores - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
This research had the general aim of apprehending the habitus of the academic field of Education Policy in Brazil, based on the study of the collective trajectory of researchers who are part of the Research Lines of Graduate Education Programs related to the field of Education Policy. The theoretical reference is based on the social theory of Pierre Bourdieu, mainly in the concepts of field (academic, intellectual, scientific and universitary), habitus, capital, politics and State. Based on this benchmark, the survey mapped, from data of the Sucupira Platform and sites of the institutions, the Graduate Programs in Education that had Research Lines related to Education Policy (year 2017). The data collection and analysis involved the descriptions of the Research Lines related to Education Policy, of the data obtained through an online questionnaire answered by 148 of the 613 professors of the Research Lines mentioned and the consultation of the Lattes Curriculum of the respondents. The methodology used for data analysis was the construction of the collective trajectory of the agents. This tool elucidates the function of the agents in the structures and makes it possible to point out the logic of the field studied, through the positioning and dispositions - habitus - of the agents. It is argued that the understanding of the logic of the academic field of Education Policy implies exploring, among other aspects: a) the profile of researchers of Education Policy; and b) the habitus of the researchers, through the analysis of the collective trajectory. The social position of the agents showed that there is a group of exponential researchers, a group of researchers, academic managers and a group of educational researchers. This social position was determined through the identification of the possession of specific capitals in the academic field of Education Policy: capital of scientific prestige and scientific power in the academic field of Education Policy. From these social positions, the researchers’ responses were analyzed comparatively. Position decisions showed similar characteristics among the agents that are in the same social position and distinct characteristics when in different social groups. The habitus, however, has revealed the scientific issues on which the agents agree (BOURDIEU, 2004d) with any of the social positions that they are part of. The apprehension of the habitus was carried out from the descriptions of the Lines of Research and the answers of the researchers through the definition of Education Policy, the objects of research of the Education Policy and the epistemologies used by the researchers in their researches. The main conclusions were: a) the research objects are related to the study of the functions (or omissions) of the State and the study of education policies, programs and reforms; b) the Marxist perspective and the strategy of combined theorization (pluralism) were the most cited by researchers as the basis of research; c) the purpose of research is seen as a contribution to decision-making in the social world; and d) research and militancy are intrinsically related and the researcher is expected to act in social practice through political participation.
Keywords: Política Educacional; Pesquisa; Pós-Graduação em Educação; Pierre Bourdieu; Education Policy; Search; Graduate studies in Education; Pierre Bourdieu; CNPQ::CIENCIAS HUMANAS::EDUCACAO